Evaluation of the interactions between human serum albumin (HSA) and warfarin or diflunisal by using molecular fluorescence using two approaches - Susana Amézqueta; Anna Bolioli Maria Bolioli; José Luis Beltrán; Clara Ràfols (International Association of Physical Chemists (IAPC), 2018)
Serum albumin is the main drug transporter of the bloodstream and contains two main binding sites:  Sudlow I or acidic drug binding site, and Sudlow II or benzodiazepine binding site. Warfarin, a well-known anticoagulant drug commonly used in the prevention of thrombosis and thromboembolism, binds to Sudlow I site, whereas non-steroidal antiinflammatory drugs (NSAIDs) such as diflunisal bind preferentially to Sudlow II site.  Albumin is a fluorophore that modifies its fluorescence (quenching or enhancement effect) when it is bound to a drug. The application of the double logarithm Stern-Volmer equation allows the calculation of the stoichiometry and the binding constant of the process. This procedure does not consider the possible interferences coming from the fluorescence of the drug though. Another strategy to evaluate the binding constants is to consider the whole spectrum, taking into account all the possible species in equilibrium; in this case we have used an extended version of the STAR program, which can deal with 300 spectra, each containing up to 300 data points. The aim of this work is to compare both approaches to evaluate the interaction between warfarin (Sudlow I) and diflunisal (Sudlow II) and HSA: the double logarithm Stern-Volmer equation and the STAR program.